Customer Trust as a Mediator of Digital Marketing Effects on Consumer Behavior: A Systematic Review - Sari, Fitrah; Rahman, Ahmad Vajri; Mirsal (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to examine the role of customer trust as a mediating variable in the relationship between digital marketing strategies and consumer behavior. As digital marketing evolves, companies are required not only to create engaging content but also to build strong trust to influence purchase intention, loyalty, and customer engagement. This research employs a systematic literature review (SLR) following PRISMA guidelines, selecting 52 empirical articles from reputable international databases such as Scopus, Web of Science, EBSCOhost, and ScienceDirect, published between 2015 and 2026. The analysis involved thematic and descriptive synthesis to assess the strength of digital marketing’s impact on customer trust and consumer behavior outcomes. The results indicate that digital marketing has a significant positive effect on customer trust formation (β=0.652; p<0.001). Customer trust functions as a partial mediator that strengthens the impact of digital marketing on purchase intention, loyalty, and engagement. The direct effect of digital marketing on consumer behavior is weaker when trust is not optimally established. These findings emphasize that effective digital marketing strategies must focus on transparency, security, credibility, and personalization to maximize consumer behavior outcomes. Practically, this study provides important implications for companies and digital marketing practitioners, highlighting that successful campaigns rely not only on content and visibility but also on the ability to build customer trust. The study also opens avenues for future research to examine more specific trust dimensions, including platform integrity, information quality, and social proof, within increasingly complex digital marketing contexts.